Intracerebral microinjection of interleukin-4/interleukin-13 reduces β-amyloid accumulation in the ipsilateral side and improves cognitive deficits in young amyloid precursor protein 23 mice - Kawahara, K.; Suenobu, M.; Yoshida, A.; Koga, K.; Hyodo, A.; Ohtsuka, H.; Kuniyasu, A.; Tamamaki, N.; Sugimoto, Y.; Nakayama, H. (Neuroscience, 2012)
We previously reported that the anti-inflammatory cytokine interleukin (IL)-4 induced selective clearance of oligomeric β-amyloid (Aβ1–42) in rat primary type 2 microglial cells. For the present study, we investigated whether IL-4 and IL-13 could activate microglial cells to induce Aβ clearance in vivo and improve cognitive deficits in APP23 mice, which are amyloid precursor protein transgenic mice. We administered an intracerebral microinjection of a mixture of IL-4 and IL-13 or of saline vehicle into one hemisphere of APP23 mice and their wild-type littermates, 4.5 and 9 months old, after which we evaluated the effects of these treatments on spatial learning and memory by Morris Water Maze test and on accumulated amounts of Aβ. The cytokine injection significantly improved memory deficits of 4.5-month-old APP23 mice, but did not do so in 9-month-old APP23 mice, even though similar Aβ reductions were observed in both age groups of APP23 mice in the ipsilateral neocortex. The cytokine injection improved memory impairment of 9-month-old wild-type (WT) mice in the probe trial. Immunohistochemical analysis of the 4.5-month-old APP23 mice revealed the presence of increased numbers of microglial cells at 2 days after the cytokine injection. In addition to induced CD36 expression in the activated microglia, increased expression of neprilysin, mainly in neurons, suggested that the cytokines improved the cognitive deficits via degradation and clearance of intra- and extraneuronal Aβ peptides, of buffer-extractable nonplaque form. Double immunostaining also revealed that most of the activated microglia had the M2-like phenotype. This unique mechanism of IL-4/IL-13–induced clearance of Aβ may provide an additional strategy to prevent and/or cure Alzheimer's disease at early stage. ▶Intracerebral injection of IL-4/IL-13 reversed memory deficits in 4.5-month-old APP23 mice. ▶The memory improvement was correlated with reduced Aβ peptides of nonplaque form. ▶The injection induced expression of CD36 in activated microglia and neprilysin mainly in neurons. ▶The activated microglia were alternatively activated M2-like cells. ▶IL-4/IL-13-induced clearance of Aβ may provide an additional strategy to prevent and/or cure AD.